Age at first gestation in bovine influences female progeny post-weaning growth and reproductive development - Lopez Valiente, Sebastian; Rodriguez, Alejandro Martin; Long, Nathan M.; Maresca, Sebastian (Elsevier, 2024)
This study investigated the impact of the age at which heifers conceive for the first time on the growth and reproductive development of their female offspring. A total of seven heifers pregnant at 15 months of age (15M), nine heifers pregnant at 27 months of age (27M) and seven multiparous pregnant cows (Adult) were used in the present trial. All dams were pregnant by AI from a single sire and managed in a single group during gestation, lactation and rearing stages. After weaning heifer calves were stocked on natural pastures. Progeny of heifers that gestated for the first time at different ages did not present differences in growth; however, progeny of 15 and 27M dams had reduced BW, longissimus muscle area and 12th fat thickness compared to progeny of adult dams (P < 0.05). Diameter of the largest follicle was greater in progeny born to Adult compared to progeny born to 15 and 27M (P = 0.04). Reproductive tract score (RTS) in heifers born to Adult at 399 days of age was greater compared to heifers born to 27M, and this category presented greater development than heifers born to 15M (P = 0.02). At 435 days of age, the heifers born to Adult had a greater percentage defined as pubertal compared to the progeny of 15 and 27M (P = 0.04). At 495 days of age, the weight of uterus, ovaries and corpora lutea were not affected by the age of dams at calving (P > 0.25). These data indicated that the age at which heifers received their first service affects female offspring growth RTS at early ages, but it does not have any impact in organ development after diet with a high energy level.